2018
DOI: 10.3354/dao03264
|View full text |Cite
|
Sign up to set email alerts
|

Role of the intertidal predatory shore crab Carcinus maenas in transmission dynamics of ostreid herpesvirus-1 microvariant

Abstract: Ostreid herpesvirus-1 microVar (OsHV-1 µVar) has been responsible for significant mortalities globally in the Pacific oyster Crassostrea gigas. While the impact of this virus on the Pacific oyster has been significant, this pathogen may have wider ecosystem consequences. It has not been definitively determined how the virus is sustaining itself in the marine environment and whether other species are susceptible. The shore crab Carcinus maenas is a mobile predator and scavenger of C. gigas, commonly found at Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…In this study, the potential for an intertidal ecosystem engineer C. edule to become infected with and to act as an alternate host of OsHV-1 μVar was determined, through field screening, laboratory transmission trials and using a variety of diagnostic methods. The field survey demonstrated the ability of a virus to jump host to an alternate infaunal bivalve with potential further transmission through an ecosystem and potentially greater geographic dispersal via trophic food webs, as was demonstrated by Bookelaar et al [42]. In that study, OsHV-1 μVar was detected in C. maenas, a predator/scavenger of C. gigas and C. edule [52], and transmission of the virus occurred between infected crabs and naïve C. gigas.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…In this study, the potential for an intertidal ecosystem engineer C. edule to become infected with and to act as an alternate host of OsHV-1 μVar was determined, through field screening, laboratory transmission trials and using a variety of diagnostic methods. The field survey demonstrated the ability of a virus to jump host to an alternate infaunal bivalve with potential further transmission through an ecosystem and potentially greater geographic dispersal via trophic food webs, as was demonstrated by Bookelaar et al [42]. In that study, OsHV-1 μVar was detected in C. maenas, a predator/scavenger of C. gigas and C. edule [52], and transmission of the virus occurred between infected crabs and naïve C. gigas.…”
Section: Discussionsupporting
confidence: 60%
“…More recently OsHV-1 μVar was detected in different marine invertebrates including the Sydney cockle Anadara trapezia in Australia [39], in cultured Mytilus galloprovinciallis in Italy [40], in wild Mytilus spp. consisting of the blue Mytilus edulis, M. galloprovinciallis and hybrids of both parent species, in Ireland [41] and the green shore crab C. maenas [42]. Bookelaar et al [42] demonstrated that transmission of the virus could occur from C. maenas, previously exposed to the OsHV-1 μVar in the wild, to cohabiting naïve C. gigas within four days.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of oysters and crabs resulted in significant reduction of PgV abundances over the 24 h experimental period, i.e. <12% and 90% respectively within 3 h. In other studies, after exposure to water containing human enteric viruses, bivalves and crabs showed internal accumulation of the viruses, with recovery of viruses from tissues such as the digestive tract [45][46][47][48][49] . This indicates that both decapods and bivalves have the potential to take up viruses from their surrounding environment and, collectively, significantly contribute to the reduction in viral abundances.…”
Section: Resultsmentioning
confidence: 70%
“…Carcinus maenas is a crustacean species native to all coasts of the UK, Ireland and North-East Atlantic. It is well known for its role as a prolific invasive to many other parts of the world [ 13 ], as well as its capacity to harbour numerous parasites and diseases [ 14 , 15 , 16 , 17 , 18 ]. Of late, parasites of C. maenas are of increasing interest and importance due to their disease status.…”
Section: Introductionmentioning
confidence: 99%